Manajemen Risiko Dalam mengoptimalkan kesetaraan gender di SMk Muhammadiyah 3 Bandung - Shoimah, Rishna; Hidayat, Wahyu (Prodi Pendidikan Agama Islam, 2024)
Gender equality in the educational environment is the main focus in efforts to create a just and sustainable society. This journal discusses the role of risk management in optimizing gender equality in schools. The risk management approach not only addresses potential risks that may arise in the implementation of gender equality policies, but also highlights opportunities that can be found through appropriate management measures. By integrating risk management into gender equality efforts in schools, this article contributes to a better understanding of how to overcome barriers and seize opportunities to create an inclusive and equitable educational environment for all students, regardless of gender.